Methods and devices for delivering exogenously generated speech signals to enhance fluency in persons who stutter - Rastatter, Michael P.; Kalinowski, Joseph Stanley; Stuart, Andrew (East Carolina University, 2004)
Methods and devices generate an exogenous natural second speech signal as an auditory stimulus to a user to enhance the fluency of persons who stutter. The natural speech signal is independent of the contemporaneous speech production of the stutterer and is provided by a voice gesture and can be a prolonged or sustained voice gesture sound such as a simple vowel, or consonant, or vowel trains and the like. The second speech signal can be transmitted in advance of a speaking event or speech production of the stutterer and/or concurrently with a speaking event, either intermittently or continuous during the speaking event. The devices of the instant invention are configured to provide the voice based speech signal such that it is audible to the user and does not require feedback of the user's own speech allowing the user to speak at a substantially normal pace with enhanced fluency. The device and methods can relay the signal based on a manual activation or automatically based on a detection of speech or a stuttering event on the part of the user.
United States patent 6,754,632
Keywords: Stuttering--Treatment--Patents; Audiology--Instruments--Patents; Stuttering--therapy